MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA CIMANGGU I, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Miftakhul Anwar; Azizah Mursyidah; Bogart Bolivian (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
Micro, Small and Medium Enterprises in Indonesia are an important part of the national economic system because they play a role in accelerating equitable distribution of economic growth through the mission of providing business and employment opportunities, increasing people's income and playing a role in increasing foreign exchange earnings and strengthening the structure of the national industry. access to sharia financing for Micro, Small and Medium Enterprises in Cimanggu Satu Village, Cibungbulang District, Bogor Regency. In this community service, activities are carried out based on the Social Intervention method. The results of this community service are a reference to how far the program implemented can run, the ability of each individual in the community and groups. trust in formal financial institutions.